Rumen fermentation and digestibility of spent mushroom (Pleurotus ostreatus) substrate inoculated with Lactobacillus brevis for Hanwoo steers - Baek, Youl Chang; Kim, Min Seok; Reddy, Kondreddy E.; Oh, Young Kyoon; Jung, Young Hun; Yeo, Joon Mo; Choi, Hyuck (Revista Colombiana de Ciencias Pecuarias, 2017)
Background: Ensiling spent mushroom substrate (SMS) generally increases its nutrient digestibility and quality. Objective: To determine the feed quality and digestibility of SMS from Pleurotus ostreatus (SMSP) inoculated with lactic acid bacteria (LAB: Lactobacillus brevis) in Hanwoo steers. Methods: Ruminal disappearance of SMSP and inoculated SMSP (ISMSP) were evaluated in three rumen-fistulated Hanwoo steers (408 ± 13.0 Kg body weight). Further, three healthy Hanwoo steers (336 ± 69.0 Kg body weight) were randomly allotted to one of three dietary treatments (control: 25% straw, 75% concentrates; treatments: 25% straw, 60% concentrates, and 15% of either SMSP or ISMSP) in a 3×3 Latin square design. Results: The chemical composition of the ISMSP diet did not differ from that of the control or the SMSP diets. In the ISMSP diet, the rate of decrease of pH of ruminal fluid and the increase in storage period was greater than with the SMSP diet. Ruminal disappearance of dry matter, crude protein, neutral detergent fiber, and acid detergent fiber were slightly higher in steers fed ISMSP than those fed SMSP. Furthermore, the degradation rate and effective degradability of crude protein was greater in the ISMSP diet than in the SMSP diet. Effective ruminal fermentation characteristics and total nutrients digestibility were not affected by SMSP nor ISMSP diet. Conclusion: The SMSP and ISMSP diets could replace formulated concentrate without adverse effects and be a cost-effective feed for Hanwoo steers. Furthermore, LAB inoculation improved the SMSP preservation.